Vegetation cover and plant diversity on cold climate green roofs - Lönnqvist, Joel; Blecken, Godecke-Tobias; Viklander, Maria (Journal of Urban Ecology, 2021)
Abstract Both vegetation abundance and community composition play important roles in functions of green roofs (e.g. stormwater retention, habitat provision, aesthetic appearance). However, green roofs’ vegetation, and hence their functions, can change significantly over time. More understanding of these changes is required, particularly in cold climates. Therefore, this study investigated vascular plant covers and species compositions on 41 roof sections located in Sweden’s subarctic and continental climate zones. For the roof sections with a known originally intended vascular plant composition (n = 32), on average 24 ± 9% of the intended species were detected in surveys, and unintended species accounted for 69 ± 3% of the species found. However, most colonizing species formed sparse cover on the roofs. Thus, they may make less contributions to green roofs’ potential functionalities related to vegetation density (e.g. social perception, effectiveness in stormwater management and thermal performance) than the intended vegetation. The intended species dominated plant cover (93 ± 3%) and Sedum acre (58 ± 36% cover) was the most commonly detected species and as found in previous studies, substrate depth was positively related to both plant cover and species richness. Contrary to a hypothesis, the roofs’ vascular plant cover was not related to species richness but was significantly and negatively correlated with moss cover. The results highlight the importance of substrate depth for both plant abundance and species diversity and show that even in a cold climate, colonizing unintended species can strongly contribute to green roofs’ species richness.